Nickel(II) complexes based on l‐amino‐acid‐derived ligands: synthesis, characterization and study of the role of the supramolecular structure in carbon dioxide capture. Issue 5 (23rd September 2020) - Rivas Marquina, Andrea; Movilla, Federico; Sánchez Montilva, Olga Carolina; Rentschler, Eva; Carrella, Luca; Albores, Pablo; Di Salvo, Florencia
Abstract : Two l ‐amino‐acid‐based Ni II complexes are reported; while the l ‐tyrosine derivative is a symmetrical μ3 ‐carbonate‐bridged self‐assembled trinuclear Ni II complex whose formation involves CO2 uptake, the l ‐phenylalanine analog is a mononuclear system which does not exhibit the same behaviour. Abstract : The formation of the symmetrical μ3 ‐carbonate‐bridged self‐assembled trinuclear Ni II complex Na2 {[Ni(LO)2 (H2 O)]3 (μ3 ‐CO3 )} (LO is the carboxylate anion of a l ‐tyrosine derivative), involves atmospheric CO2 uptake. The asymmetric unit of the complex comprises an octahedral coordination for the Ni II with two l ‐tyrosine‐based ligands, a water molecule and one O atom of the carbonate bridge. The Ni3 –μ3 ‐CO3 core in this compound is the first reported of this kind according to the Cambridge Structural Database (CSD). The supramolecular structure is mainly sustained by hydrogen bonds developed by the phenolic functionality of the l ‐tyrosine moiety of one ligand and the carboxylate group of a neighbouring ligand. The crystal packing is then characterized by three interpenetrated supramolecular helices associated with a diastereoisomer of the type R ‐ sup P, which is essential for the assembly process. Magnetic susceptibility and magnetization data support weak ferromagnetic exchange interactions within the novel Ni3 –μ3 ‐CO3 core. The Ni II complex obtained under the same synthetic conditions but using the analogous ligand derived from the amino acid l ‐phenylalanine instead of l ‐tyrosine gives rise to to a mononuclear octahedral system. The results obtained for the different complexes demonstrate the role of the supramolecular structure regarding the CO2 uptake property for these Ni II –amino‐acid‐based systems.